Coaxially electrospun heparin-eluting scaffolds for vascular graft application - Krause, Gerhard Jaco (Department of Human Biology, 2023)
The use of electrospun scaffolds for small diameter vascular grafts (< 6 mm) has shown promise in the search for alternative solutions, as current synthetic grafts have high failure rates. The inclusion of heparin into such scaffolds can be beneficial for vascular graft applications as it could prevent mid-graft thrombosis, stabilise and potentiate growth factors as well as subdue undue proliferation of smooth muscle cells. Previous attempts at including heparin by chemical modification or inclusion into the bulk of the electrospun fibres (blend or emulsion electrospinning) were successful but resulted in burst release, reduced bioactivity and rapid elution of the heparin due to bulk degradation of the polymers. This project aimed to develop scaffolds comprising electrospun degradable polyurethane fibres with coaxially incorporated heparin sodium (HepNa+ ) with improved release kinetics and heparin activity for application in the tissue engineering of blood vessel substitutes. Scaffold sheets were cut from tubes (ID = 25 mm) produced on a rotating mandrel by coaxial, conventional and blend electrospinning of a degradable polyurethane, DegraPol® (DP30). Three coaxially electrospun groups were produced with DP30 (CHCl3) shells and polyethylene oxide, PEO (H2O/EtOH) cores containing either low (0.3 wt%), high (0.6 wt%) or no HepNa+ . Blend electrospinning was achieved by incorporating heparin (after modification to its tributylamine (TBA) salt for solubility) into DP30 solution (in CHCl3). Lastly, a control group was produced by conventional electrospinning of DP30 (CHCl3). The morphological (fibre diameter, fibre orientation, pore size and porosity), mechanical (tensile stress and strain, suture retention) and thermal (glass transition, melting and crystallization temperature) properties of the scaffolds were characterised and the corresponding in vitro drug release (heparin quantification and activity) and degradation response over 6 weeks in PBS (37 °C) were determined. Subsequently, conditions were optimised in a pilot study to electrospun small diameter (ID = 2.6 mm) tubular grafts and their morphological and mechanical properties (hoop stress, burst pressure and compliance) were determined. Coaxial electrospinning of DP30 with a water core and especially the addition of HepNa+ resulted in a decrease in fibre diameter (40 %), OI (23 %), pore size (39 %) and porosity (20 %) (all P < 0.05), most likely due to increased conductivity and dielectric constant. With one exception, there was no difference in the directional tensile properties between scaffold groups (ultimate tensile stress > 0.9 MPa, maximum strain > 100 %, suture retention > 2.4 N) or within groups between the longitudinal and circumferential tensile properties. After 6 weeks of in vitro degradation, all groups exhibited similar mechanical losses of approximately 40 % in ultimate tensile stress and 80 % in maximum elongation in circumferential and longitudinal directions. The smaller vascular grafts had burst pressures superior to native vasculature and compliances approximating those of healthy arteries. Thermal analyses (DSC) of the different groups showed similar thermograms with little intergroup variation and indicated that the electrospinning process did not unduly affect the thermal properties or crystallinity, of DP30. There was also no major variations in thermograms of degraded samples. Blend electrospun scaffolds showed the expected initial burst release of HepTBA (47.7 %, 3 days) followed by a sustained release (56.1 %, 6 weeks). Coaxially incorporated HepNa+ also exhibited initial burst release (67.5-69.7 %, 3 days) for both the low and high heparin content groups followed by improved sustained release (81.9 - 97.7%, 6 weeks). Coaxial incorporation had a 2× higher heparin encapsulation efficiency than blend incorporation (approaching 100 %). Heparin, post-TBA-modification, did not fully retain its antithrombotic properties (54.9 % reduction), which was further reduced after incorporation and release (24.2 % reduction). HepNa+ , however, retained its full antithrombotic activity post coaxial incorporation and elution. Coaxial electrospinning of heparin in DP30 shows potential for producing small diameter vascular grafts with mechanical properties comparable to small blood vessels. Although some initial burst release occurred, the sustained release over 6 weeks, incorporation of heparin without the need for modification at improved efficiency, and the retained activity of the heparin after electrospinning incorporation and elution; holds promise for vascular graft applications. Future work should aim for the production of continuous cores within fibre morphology and evaluating graft performance in an in vivo model to determine whether an appropriate and sufficient amount of heparin has been included to affect the desired response.